Sistem Informasi Pencatatan dan Pembayaran Layanan Medis Menggunakan Metode Rapid Application Development pada Praktik Mandiri Dokter - Lusia Rohyahni; Hery Sunandar; Syafriadi Syafriadi (Computer Journal, 2026)
Dr. Erni Safrita’s private practice still records patient data, examinations, medications, payments, and reports manually. This causes delays in data retrieval, recording errors, payment calculation errors, and difficulties in administrative reporting. This study aims to develop a Medical Service Recording and Payment Information System using the Rapid Application Development (RAD) method. Data were collected through observation, interviews, documentation, and literature review involving a doctor and one staff member. The system was designed using Unified Modeling Language (UML) and implemented with Microsoft Visual Basic 2010 and MySQL. The system provides user authentication, patient and medication management, examination recording, payment processing with automatic cost and change calculations, and period-based report generation. Black-box testing using 11 scenarios showed that all scenarios functioned successfully, achieving a 100% success rate. The results indicate that the system supports medical service recording, payment processing, and administrative reporting in a more structured and computerized manner.